STUDI PERFORMA BRIKET AMPAS KOPI DENGAN CAMPURAN SERAT SAWIT DENGAN PEREKAT SARI BUNGA SEPATU (Hibiscus Rosa-Sinensis) - Denas, Fahrezi; Handra, Nofriady (Ensiklopedia of Journal, 2025)
In the future, world energy will be threatened by the increasing difficulty of finding energy sources from fossils. Experts argue that with current consumption patterns, fossil energy is expected to run out soon. Petroleum will run out in 30 years in 2052,.This study aims to determine the performance of briquettes from coffee grounds waste mixed with EFB (Empty Fruit Bunch) fiber and glued using hibiscus rona-sinesis flower extract as a natural adhesive. Variations in the ratio of coffee husk and EFB mixture (9:1, 8:2 7:3) were used to test the physical and chemical characteristics of briquettes, including density, water content, volatile matter, fixed carbon, calorific value, and ash content, which were compared with Indonesian national standards (SNI 01-6235-2000). The results showed that increasing the proportion of coffee grounds increased the calorific value of the briquettes, but the fixed carbon and volatile matter values did not meet the established standards. Other parameters such as water and ash content had met the national standards. The average density of briquettes ranges from 0.39–0.40 g/cm³, with a mixture ratio of 9:1 producing the highest calorific value, which is 4,625 cal/gram.Keywords  : Briquettes, Biomass, Calorific value, Hibiscus extract, Coffee grounds, Empty Fruit Bunch (EFB)